Transformational Leadership Competence of Principals in Improving Teacher Performance - Septana Nur Hidayat; Bambang Sumardjoko; Ahmad Muhibbin (research, training and philanthropy institution Natural Aceh, 2023)
This article aims to explain the competence of transformational leadership of school principals in improving teacher performance at Daarul Qur'an Karanganyar Science High School. This research method includes qualitative research with an ethnographic design. The data extracted in this research is information and documents about the transformational leadership competencies of school principals, including ideal influence, intellectual stimulation, inspirational motivation, and attention to individuals to improve teacher performance. Data collection techniques used are observation, interviews, and documentation. The results of this study, namely, the principal of the Daarul Qur'an Karanganyar Science High School showed that he had a powerful category of ideal influence competence, a substantial variety of Intellectual Stimulation competence, a strong type of inspirational motivation competence, a potent class of attention competence towards individuals. The results of the teacher performance assessment of 20 teachers considered to have scored in the excellent category. This study concludes that school principals understand their leadership competencies in improving teacher performance as Hendrayadi's theory, namely ideal influence, intellectual stimulation, inspirational motivation, and attention to individuals. The principal's efforts to improve teacher performance are (a) motivating teachers, (b) increasing teacher discipline, (c) creating a conducive working atmosphere, and (d) increasing teacher competence. The implication of this research is as input to school principals in improving the performance of Daarul Qur'an Karanganyar Science High School teachers